ESTUDO COMPARATIVO ENTRE OS TESTES ADOTADOS PELO PNCEBT PARA O DIAGNÓSTICO SOROLÓGICO DA BRUCELOSE EM BOVINOS* - Meirelles-bartoli, R.b. [UNESP]; Mathias, L.a. [UNESP] (Instituto Biológico, 2020)
Serum samples from 1,061 bovine were analyzed by serological diagnostic techniques adopted by the Brazilian Program for Animal Brucellosis and Tuberculosis Control and Eradication in order to compare, as a screening test, the rose Bengal plate test (RBPT), and as confirmatory tests, the 2-mercaptoethanol plus standard tube agglutination test (2-ME), and the complement fixation test (CFT). Relative sensitivity of 99.6%, 98.8% and 91.1% were observed, respectively, for RBPT, 2-ME and CFT, and relative specificity of 83.9%, 96.2% and 100.0%. The agreement between tests was analyzed by the kappa statistic (2-ME cut-off = titer 25, and CFT cutoff = titer 4). RBPT showed a substantial agreement (kappa: 2-ME = 0.80; and RFC = 0.73) with the confirmatory tests, and excellent agreement between the confirmatory tests (kappa = 0.86) was observed. However sera with a negative result in one of the confirmatory tests and a high titer in the other were observed, reinforcing that the serological diagnosis of bovine brucellosis is more reliable when based on the results of several tests.

Avaliaram-se comparativamente as provas do antígeno acidificado tamponado (AAT), a combinação das provas de soroaglutinação lenta e 2-mercaptoetanol (2-ME) e a reação de fixação de complemento (RFC), provas preconizadas pelo Programa Nacional de Controle e Erradicação de Brucelose Tuberculose (PNCEBT). Para tanto, foram alisadas 1.061 amostras de soros bovinos. Os dados foram analisados pelo indicador kappa, adotando-se como ponto de corte o título 25 no 2-ME e 4 na RFC. Constatou-se sensibilidade relativa de 99,6%, 98,8% e 91,1%, respectivamente, para o AAT, a 2-ME e a RFC, e especificidade relativa de 83,9%, 96,2% e 100,0%. A comparação entre os testes adotados pelo programa apontou concordância boa entre o teste de triagem (AAT) e os testes confirmatórios (kappa: 2-ME = 0,80; e RFC = 0,73) e concordância ótima quando os testes confirmatórios foram comparados entre si (kappa = 0,86). No entanto foram encontrados soros com título elevado em um dos testes confirmatórios e resultado negativo no outro, o que reforça a ideia de que o diagnóstico sorológico da brucelose é mais confiável quando obtido por meio dos resultados de vários testes.
COMPARATIVE STUDY OF SEROLOGICAL TESTS FOR BOVINE BRUCELLOSIS DIAGNOSIS ADOPTED BY THE BRAZILIAN PROGRAM FOR ANIMAL BRUCELLOSIS AND TUBERCULOSIS CONTROL AND ERADICATION
Keywords: Bovine brucellosis; serodiagnosis; agreement; sensitivity; specificity; Brucelose bovina; diagnóstico sorológico; concordância; sensibilidade diagnóstica; especificidade diagnóstica